TOPIK BALANCE SCORECARD DALAM LITERATUR AKUNTANSI DI INDONESIA: STUDI BIBLIOGRAFI - Maya Aulia Saputri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This study aims to enrich the literature on performance assessment using the Balance Scorecard with the Charting The Field method. This study uses article data from 7 journals totaling 24 article with the key word